Transformative learning in open distance and e-learning: the critical role of nurse educators - Gisela Hildegard van Rensburg; Vhothusa Edward Matahela (Discover Education)
Abstract Transformative learning within Open Distance and e-Learning (ODeL) environments brings about profound changes in students’ perspectives through critical reflection and self-directed learning. It allows students to challenge assumptions, embrace inclusivity, and integrate theory into practice. Transformative learning in nursing education in the ODeL context is underexplored, particularly nurse educators' fostering of critical reflection and inclusive, student-centered learning amidst virtual challenges. This study explores the meaning of transformative learning in ODeL nursing education and examines how nurse educators can facilitate such learning. A scoping review methodology, guided by Arksey and O’Malley’s framework and the Joanna Briggs Institute guidelines, was adopted. The study was underpinned by the Transformative Learning Theory and Freire’s Critical Pedagogy. Data were synthesized from nine peer-reviewed studies published between 2014 and 2024. Three central themes emerged: the meaning of transformative learning in ODeL, barriers to its facilitation, and the transformative role of nurse educators. Transformative learning is essential in nursing education, especially in ODeL, as it equips students with critical reflection, adaptability, and collaborative skills necessary for addressing complex healthcare challenges. The review emphasizes that transformative learning in ODeL demands a human-centered, innovative, and systemic approach, rather than a simple transfer of traditional methods to online platforms. It underscores the critical role of nurse educators as facilitators of change who must model empathy, critical thinking, and adaptability to prepare students for inclusive, participatory, and contextually responsive healthcare delivery.